Relationship between domestic violence during pregnancy with breastfeeding - Dolatian, M; Hesami, K; Shams, J; Alavi-Majd, H (Advances in Nursing & Midwifery, 2008)
Background Domestic violence against women is now widely recognized as an important public health problem. The effects of it are of critical importance during pregnancy because the consequences are not limited to the woman but extend to her fetus and, later, her newborn. Evidence suggests that violence can also affect the ability of women for breastfeeding. Purpose The aim of this prospective cohort study was to evaluate the relationship between domestic violence during pregnancy with breastfeeding women referring to a healthcare center at Marivan in 2007. Methods 240 women taking prenatal care were selected through a two-stage sampling process. At first, pregnant women were assessed during the last month of pregnancy for violence by a screening questionnaire and divided into two groups: violated and non-violated. Then, they were followed up postnatally in terms of feeding routes after 4-6 weeks. Results The prevalence rates of sole breast-feeding, mixed feeding and artificial feeding within 4 weeks after delivery were 52.1%, 47.5% and 4% respectively. No significant difference in the nutrition type was found between those with the experience of sexual and emotional violence than non-violated women. However, women with the experience of physical violence had a significantly lower rate of sole breast-feeding than mixed feeding or artificial feeding groups (P=.006). Conclusion The results suggest that physical violence during pregnancy can affect breast-feeding routes. Accordingly, midwives are in a key position for detection and intervention to encourage successful breastfeeding practice. Keywords: Domestic violence, Pregnancy, Breast-feeding.